Collagenase does not persist in human islets following isolation. - Cross, S; Hughes, S; Clark, A; Gray, D; Johnson, P (2012)
Optimal human islet isolation requires the delivery of bacterial collagenase to the pancreatic islet-exocrine interface. However, we have previously demonstrated the presence of collagenase within human islets immediately following intraductal collagenase administration. This potentially has significant implications for patient safety. The present study aimed to determine if collagenase becomes internalized into islets during the isolation procedure and if it remains within the islet postisolation. Islet samples were taken at various stages throughout 14 clinical human islet isolations: during digest collection, following University of Wisconsin solution incubation, immediately postisolation, and after 24 h of culture. Samples were embedded in agar, cryosectioned, and then assessed by immunolabeling for collagenase and insulin. Immunoreactivity for collagenase was not observed in isolated islets in any preparation. Collagenase labeling was detected in one sample taken at the digest collection phase in one islet preparation only. No collagenase-specific labeling was seen in islets sampled at any of the other time points in any of the 14 islet preparations. Collagenase that enters islets during intraductal administration is washed out of the islets during the collection phase of the isolation process and thus does not remain in islets after isolation. This observation alleviates some of the important safety concerns that collagenase remains within islet grafts.